La adquisición del movimiento del verbo en las interrogativas directas e indirectas del español no nativo. - Andreeva Laguardia, Biana. (University of Ottawa (Canada), 1997)
In this thesis we investigate the acquisition of V-movement in matrix and subordinate clauses and its consequences for the position of the subject in the Spanish interlanguage of native speakers of English and French. We have specifically investigated whether or not there is parameter resetting when the value of the parameter differs in the L1 and the L2. In order to determine our subjects' non-native competence we have obtained cross-sectional data in the form of oral spontaneous production and grammaticality judgments. The results suggest that learners do not reset the V-movement parameter when they acquire Spanish as a second language, a conclusion which is in line with an emerging view about parameter resetting in second language acquisition.
Keywords: Language, Modern.